Synthesis of novel heteromacrocyclic compounds - Bradley, David (Trinity College (Dublin, Ireland). School of Chemistry, 2005)
Macromolecular systems containing pyridine subunits have been the focus of much attention. The availability of the lone-pair electrons of the pyridine nitrogen atom makes these moieties particularly attractive as chelating units in supramolecular assemblies, novel catalysts, artificial enzymes, and transition metal ligands. In substituted pyridines, the availability of the lone-pair electrons is strongly influenced by the nature of the substituents on the pyridine ring. 4-Dimethylaminopyridine (DMAP) constitutes an electron-rich pyridine ring and has been widely used as an acylation catalyst. Macrocyclic systems containing pyridine or DMAP moieties may therefore be expected to display interesting catalytic and/or ion-binding properties.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin